Child Rights-Based Analysis of Children without Parental Care in Lesotho - Pius T. Tanga; Magdaline Tanga; Perpetua L. Tanyi (Social Work and Society, 2018)
In 1989, governments worldwide promised all children the same rights by adopting the UN Convention on the Rights of the Child. The Convention changed the way children were viewed and treated - in other words, as human beings with a distinct set of rights instead of as passive objects of care and charity. The objective of this paper was to undertake a child-based rights analysis to arrive at a better understanding of the meaning and number of children without parental care, the major reasons for lack of, and specific risks of children without, parental care. In addition, the paper also explored the rights violations faced by children without parental care and factors associated with child rights violations in Lesotho. Data was collected using a stakeholders' focus group discussion that was split into two groups and held simultaneously. The findings reveal that although there was a consensus on the meaning of children without parental care, there were different understandings leaning towards the professional orientations of the participants. It was found that there were about 175,650 children without parental care in Lesotho, while the vast majority (more than130, 000) were HIV and AIDS orphans. Most of these children lack basic needs and the specific risks with children living without parental care are numerous and include the following: struggling with drug and alcohol abuse and committing other delinquent acts; vulnerability to sexual abuse and different types of exploitations. The findings also indicate that the rights of these children regarding participation, provision and protection as enshrined in the UNCRC 1989 are most often violated by both family and community members. Consequently, the children suffer from property grabbing, poverty, food insecurity, dropping out of school and poor academic performance. The paper ends with some policy recommendations to enhance family, community, civil society and government's role in ensuring the rights of children without parental care.